Effects of build direction and heat treatment on creep properties of Ni-base superalloy built up by additive manufacturing. (1st March 2017) - Kuo, Yen-Ling; Horikawa, Shota; Kakehi, Koji
Abstract: The effects of build direction and heat treatment on the creep properties of Ni-base superalloy fabricated by additive manufacturing were examined at 650 °C. The creep rupture lives and ductilities of materials produced by additive manufacturing were lower than those of conventionally wrought material. The horizontal-direction specimen exhibited inferior creep life and worse ductility than the vertical-direction specimen because of the direction of the interdendritic δ-phase precipitates, which were arrayed perpendicular to the stress axis in the former specimen. The morphology and a row of interdendritic δ-phase with incoherent interfaces were found to affect the materials' creep life and ductility. Graphical abstract: